Pengaruh metode diskusi kelompok terhadap hasil belajar siswa kelas VII tentang klasifikasi makhluk hidup di MTs Nurul Huda Malang Nengah Tangerang - Lestari, Syifa Ayu; Fitri Rizkiyah; Ani Nikmah; Rizqi Nur Rachmawati; Mona Anju Sansena (Universitas Garut, 2025)
The group discussion method is a learning approach involving verbal interaction among students to achieve common goals, such as understanding concepts, solving problems, or making decisions. This study aims to analyze the effect of the group discussion method on students’ learning outcomes in the topic of classification of living things. The research employed a quantitative approach with a Pretest-Posttest control group design, involving 50 students from MTs Nurul Huda Malangnengah, Tangerang. The research instruments were tested through validity and reliability tests, while prerequisite tests included normality and homogeneity tests. Hypothesis testing was conducted using the t-test. The results showed that the group discussion method had a significant effect on improving learning outcomes, as evidenced by a t-test significance value of 0.000 < 0.05. The average Pretest score of 53 increased to 77.2 in the Posttest after the treatment was given. These findings indicate that the group discussion method not only effectively enhances conceptual understanding but also fosters active student engagement, contributing to more effective learning. This study strengthens the empirical evidence that collaborative interaction in science learning can improve students’ learning outcomes compared to conventional methods. Keywords: Group Discussion Method, Learning Outcomes, Classification of Living Things